PENGGUNAAN ALAT PRAKTIKUM MESIN ATWOOD BERBASIS ARDUINO TERHADAP HASIL BELAJAR DAN KETERAMPILAN ARGUMENTASI MAHASISWA PENDIDIKAN FISIKA PADA MATA PRAKTIKUM MEKANIKA TAHUN AKADEMIK 2017/2018 - Fajri, Gina Lailatul; Suseno, Nyoto; Salim, M. Barkah (Universitas Muhammadiyah Metro, 2020)
Abstract: The results of the presurvey conducted at the Laboratory of Physics Education, University of Muhammadiyah Metro that there is an arduino-based atwood machine practicum tool that has been made by Rohmah (2017) and has been validated with good accuracy but this tool has not been used in learning and has several advantages one of which is automatic detect the time needed for objects to move, so that the tool can work well and can be used to find out learning outcomes and argumentation skills. The research subjects were 12 students of Muhammadiyah Metro University physics education. Data collection instruments use student worksheets and test questions. The results showed that the use of arduino-based atwood machine practicum tools could affect the learning outcomes and argumentation skills of physics education students. Learning outcomes were calculated using a t-test with a significance level of 5%, so the results showed that thit abel t table was 5.66 ≥ 2.07, thus rejecting hypothesis H0 and accept H1: (there is a difference between the pretest and posttest scores) the disputes are 21.61. Then for student argumentation skills obtained an average percentage value of 83.33% from three aspects, namely claim, evidence and reasoning. Suggestions for readers, can be used as reference media for atwood machine practicum tools in learning with different materials and other learning methods.